A Worksite Nutrition Intervention is Effective at Improving Employee Well-Being: A Pilot Study - Jay T. Sutliffe; Mary Jo Carnot; Joel H. Fuhrman; Chloe A. Sutliffe; Julia C. Scheid (Journal of Nutrition and Metabolism)
Background. Worksite dietary interventions show substantial potential for improving employee health and well-being. The aim of this pilot study was to determine the effect of a worksite nutrition intervention on improving well-being. Methods. Thirty-five university employees participated in a 6-week nutrition intervention. The dietary protocol emphasized the daily consumption of greens, beans/legumes, a variety of other vegetables, fruits, nuts, seeds, and whole grains, referred to as a micronutrient-dense, plant-rich diet. Participants were encouraged to minimize the consumption of refined foods and animal products. Results. Significant improvements in sleep quality, quality of life, and depressive symptoms were found. Conclusions. Findings reveal that a worksite nutrition intervention is effective at improving sleep quality, quality of life, and depressive symptoms with a projected improvement in work productivity and attendance.